A Lab Model for Symptom Exaggeration: What do we Need?. Issue 1 (April 2017) - Niesten, Isabella J. M.; Merckelbach, Harald; Van Impelen, Alfons; Jelicic, Marko; Manderson, Angel; Cheng, Minyi
This article reflects on the current state of the art in research on individuals who exaggerate their symptoms (i.e., feigning). We argue that the most commonly used approach in this field, namely simply providing research participants with instructions to overreport symptoms, is valuable for validating measures that tap into symptom exaggeration, but is less suitable for addressing the theoretical foundations of feigning. That is, feigning serves to actively mislead others and is done deliberately. These characteristics produce experiences (e.g., feelings of guilt) in individuals who feign that lab research in its current form is unable to accommodate for. Paradigms that take these factors into account may not only yield more ecologically valid data, but may also stimulate a shift from the study of how to detect feigning to more fundamental issues. One such issue is the cognitive dissonance (e.g., feelings of guilt) that – in some cases – accompanies feigning and that may foster internalized fabrications. We present three studies (N's = 78, 60, and 54) in which we tried to abate current issues and discuss their merits for future research.